Optimized method for murine bone marrow collection, fixation and staining for microscopic evaluation. (2nd January 2016) - Van Hoy, Marjie; Larson, Monika; Nunez, Victor; Martzall, Angela; Leong, Laurie; Foreman, Oded; Katavolos, Paula
Abstract : Murine bone marrow smear examination can be requested as a supplemental parameter to assist in the identification of hematotoxic effects of a new compound or to confirm known target biology on hematopoiesis. Cellular heterogeneity and the presence of cells at variable developmental stages challenges the identification of cell lineages and the accurate interpretation of cytomorphologic changes even in an ideally processed and stained bone marrow slide preparation. Optimal microscopic evaluation of bone marrow is predicated on a standardized technique for quality sample collection, slide preparation, cellular fixation, and staining. To determine an optimal protocol for murine bone marrow slide preparation, potential factors influencing slide quality were examined including: method of cell harvest, smear preparation technique, interval from sample collection to processing, addition/absence of protein, and tinctorial characteristics of standard cytochemical stains. This research communication describes the effect of these tested variables on bone marrow slide quality and outlines an optimized procedure to prepare murine bone marrow smears for cytologic evaluation using a cytocentrifugation technique.